Effect of teenage parenthood on mental health trajectories: does sex matter? - Biello, Katie Brooks; Sipsma, Heather L; Kershaw, Trace (American journal of epidemiology, 2010)
Rates of teenage pregnancy and parenthood in the United States remain high. Although many consequences of teenage parenthood have been well studied, little prospective research has examined its effect on mental health. This study aims to better understand the impact of teenage parenthood on mental health and to determine whether sex modifies this relation. Using data from the National Longitudinal Survey of Youth, 1997 (1997-2006), and a matched cohort design, the authors compared changes in the mental health of parenting teenagers and nonparenting teenagers over 6 years of follow-up with mixed-effects regression. The results indicate that mental health improved for all teenagers over 6 years of follow-up. Furthermore, overall, teenage parenthood was not associated with changes in mental health; however, sex modified this relation. Although the mental health of teenage fathers improved at a faster rate compared with nonparenting teenage males, teenage mothers improved at a slower rate compared with nonparenting teenage females. Psychological health has important implications for both the teenage parent and the child. Future studies should aim to better understand the mechanisms through which teenage parenthood impacts mental health among both males and females, and interventions should be developed to ensure mental health among young parents.
Keywords: Adolescent; Child; Ethnic Groups; Female; Humans; Male; Mental Disorders; Parenting; Pregnancy; Pregnancy in Adolescence; Sex Factors; Socioeconomic Factors